(untitled) (The Peerian Journal, 2022)
In the post-World War II years, Uzbekistan began construction of large irrigation facilities. This process was carried out in accordance with the orders of the Central Committee of the CPSU (b) and the Council of People’s Commissars of the USSR issued in July 1945 and February 2, 1946. The period of construction of huge irrigation networks has begun in Surkhandarya region.